Numerical Simulation of Entropy Generation For Casson Fluid Flow Through Permeable Walls And Convective Heating With Thermal Radiation Effect - Martins, O.A. (Serbian Society of Computational Mechanics, 2020)
In this work, the influence of entropy generation analysis for an electrically conducting Casson fluid flow with convective boundary conditions has been numerically studied. The governing equations are analyzed numerically using weighted residual methods. Subsequently, the residuals were minimized using two different approaches of weighted residual method namely collocation weighted residual method (CWRM) and Galerkin weighted residual method (GWRM) and computed numerically using mathematical software. The impacts of governing parameters on Casson flow velocity, temperature profile, local skin friction, and Nusselt number were analysed. The obtained solutions were used to determine the heat transfer irreversibility and bejan number of the model. The results of the computation show that the effect of thermophysical properties such as thermal radiation parameter, suction/injection parameter, magnetic field parameter, radiation parameter, and Eckert number has a significant influence on Skin friction coefficient ( Cf) and local Nusselt number ( Nu) when compared to the Newtonian fluid. The findings from this study are relevant to advances in viscoelasticity and enhanced oil recovery. Â© 2020. All Rights Reserved.